O Congresso e a política externa: um estudo sobre a Câmara dos Deputados brasileira no Governo Lula - Helga do Nascimento de Almeida (2013)
Latin America is often described as a continent in which the countries' foreign policy are built primarily by executive. To investigate the production of legislative decisions in the area of Brazil's foreign policy is possible to perceive the existence of conventional wisdom too. It is stated, in most cases without presenting consistent empirical evidence that the legislature plays a role only ratifying the executive branch in foreign policy. This recurring vision - which holds that the action of the Legislature would seal automatic international acts agreed - with wide or full autonomy by the Executive - definitely contributes to the lack of systematic research on this subject. Contrary to what is reported by this conventional wisdom, this paper starts from the observation that there are tools available that are actually used by the Legislature for policy (agenda setting) foreign policy - some ex-ante, ex-post others the start of processing of materials. The central question of this work is: The Legislature, through the use of agenda powers conferred to it by the Constitution of 1988 and the Internal Rules of the Chamber 7 of Deputies, has managed to be assertive with regard to propositions related to the sphere of foreign policy? This research covers the study of all kinds of propositions that were considered in the government of President Luiz Inácio Lula da Silva in an attempt to regulate foreign policy. Among these propositions include those presidential messages, bills and ordinary complementary proposals for the inspection and control and legislative decrees. In order to contribute more effectively to the literature of the area, this research, which can be classified as descriptive, mobilized a series of empirical data that possibly had not been explored and may rather present consistent evidence of the participation of Power legislature in Brazilian foreign policy.